2016
DOI: 10.1177/1354816616654254
|View full text |Cite
|
Sign up to set email alerts
|

A regional analysis of willingness-to-pay in Asian cruise markets

Abstract: This article tests whether the willingness-to-pay (WTP) of cruise tourists is affected by multivariables, namely regional level variables, socio-demographic variables, cruise perception variables, cruise motivations and cruise preferences. Our research aims to measure the influence of the multivariables on the WTP of cruise tourists, in order to trace the determinants of WTP. Using a censored regression model, the following variables are found to be highly associated with the WTP of cruise tourists: income, ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Transportation is a critical component of successful tourism development. Although a plethora of studies have examined transportation to destinations, scant research has examined intra-city mobility including travelling around a city, visiting urban attractions, and returning to accommodations (Chen, Zhang, et al, 2016). Consequently, Chen, Neuts, et al (2016) have suggested the importance of understanding tourists' motivations, preferences, and intentions related to using tourism transportation at destinations.…”
Section: Ride-sharingmentioning
confidence: 99%
“…Transportation is a critical component of successful tourism development. Although a plethora of studies have examined transportation to destinations, scant research has examined intra-city mobility including travelling around a city, visiting urban attractions, and returning to accommodations (Chen, Zhang, et al, 2016). Consequently, Chen, Neuts, et al (2016) have suggested the importance of understanding tourists' motivations, preferences, and intentions related to using tourism transportation at destinations.…”
Section: Ride-sharingmentioning
confidence: 99%
“…The application of WTP in tourism research has mainly focused on determining the amount of WTP and the factors driving the paying preference or amount (e.g., Chen, Zhang, & Nijkamp, 2016) in various contexts, including natural attractions such as natural parks and rainforests (e.g., Reynisdottir, Song, & Agrusa, 2008), outdoor recreation activities (Asafu-Adjaye & Tapsuwan, 2008), natural resource management and conservation (e.g., Piriyapada & Wang, 2015) and green tourism products (Hinnen, Hille, & Wittmer, 2015). These studies have identified a series of WTP determinants in different contexts and mapped the demand curve and elasticity patterns based on WTP values.…”
Section: Valuation Of Non-market Goods and Wtpmentioning
confidence: 99%
“…Following Armbrecht (2014), the final WTP amount was decided based on the median value of each interval. Other studies have used a similar MPL method with a set of interval consistent estimators (e.g., Chen, Zhang, & Nijkamp, 2016). For those who selected zero for at least one of the flight classes, a follow-up question was asked about the reason.…”
Section: The Datamentioning
confidence: 99%
“…In the survey design, the inclusion of price as an attribute permits a multidimensional valuation surface to be assessed for cost–benefit analysis (Hanley, 2001). The use of WTP and economic welfare indicates that attribute-based methods differ from other applications of conjoint analysis (Chen et al, 2016; Holmes et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%